Exploring Health-Related Quality of Life Burden in Peanut Allergy and the Potential Benefit of Oral Immunotherapy: Estimation of Health State Utility Values for Children and Adolescents and Their Caregivers - Gallop K; Acaster S; de Vries J; Browne R; Ryan R; Baker S; Du Toit G (Patient Preference and Adherence, 2022)
Katy Gallop,1 Sarah Acaster,1 Jane de Vries,2 Richard Browne,2 Robert Ryan,2 Sarah Baker,3 George Du Toit4 1Acaster Lloyd Consulting Ltd, London, UK; 2Aimmune Therapeutics, London, UK; 3Anaphylaxis Campaign, Farnborough, UK; 4Department of Paediatric Allergy, Division of Asthma, Allergy and Lung Biology, MRC & Asthma UK Centre in Allergic Mechanisms of Asthma, King’s College London, Evelina London Children’s Hospital, Guy’s and St Thomas’ NHS Foundation Trust, London, UKCorrespondence: Katy Gallop, Acaster Lloyd Consulting, 84 Theobalds Road, London, WC1X 8NL, UK, Tel +44 203 9781686, Email katy.gallop@acasterlloyd.com Robert Ryan, Aimmune Therapeutics, 10 Eastbourne Terrace, London, W2 6LG, UK, Email rryan@aimmune.comPurpose: This study aimed to estimate utility values for health states relating to oral immunotherapy (OIT) for peanut allergy (PA), for children with PA and their caregivers.Patients and Methods: Two methods were used: an online survey and structured interviews. Both methods assessed current utility/untreated PA (health-related quality of life, HRQoL) and HRQoL in different health states: “up-dosing phase of treatment”, “maintenance phase” and “able to tolerate 6– 8 peanuts if accidentally ingested”. The survey was conducted in individuals with and without experience of OIT; data collected included the EQ-5D-Y (child states) and EQ-5D-5L (caregiver states).Results: In total, 100 caregivers and 38 adolescents completed the treatment-naïve survey, a separate sample of 50 caregivers participated in structured interviews. Seven caregivers and two adolescents with experience of OIT for PA completed the survey. Data from the three samples were pooled, the mean utility values were untreated PA: 0.796 (child), 0.855 (caregiver); up-dosing: 0.711 (child), 0.806 (caregiver); maintenance: 0.821 (child), 0.849 (caregiver), tolerate 6– 8 peanuts: 0.859 (child), 0.884 (caregiver). The results show a gain in utility of 0.063 for children and 0.029 for caregivers between the untreated and tolerate 6– 8 peanuts health states.Conclusion: This study is the first to assess utilities relating to OIT for PA. The results show the potential benefit of OIT for individuals with PA and their caregivers and provide values for use in cost-effectiveness evaluation.Keywords: peanut allergy, oral immunotherapy, health-related quality of life, health state utilities, caregiver